Endolenfatik kese tümörü - (:unkn) unknown (My University, 1999)
Temporal kemiğin papiller tümörleri çok nadir ve agresif neoplazmlardır. Son yıllarda endolenfatik kese kaynaklı oldukları gösterilmiştir. Lokal-invaziv, destrüktiv ve hipervasküler tümörlerdir. Tedavi lezyonun tamamının çıkarılmasıdır; ancak ileri tümörlerde subtotal eksizyon önerilebilir. Çalışmamızda, sol kulağında işitme kaybı ile başvuran 50 yaşında bir erkek hastada endolenfatik kese tümörünün cerrahi tedavisi sunulmuştur.

Papillary tumors of the temporal bone are very rare but aggressive neoplasms. Recently, they have been shown to originate within the endolymphatic sac. They are locally-invasive, destructive and hypervascular. The treatment of choice is total removal of the lesion; however, complete excision of advanced lesions is nearly impossible. We report a case of endolymphatic sac tumor in a 50-year-old man who presented with left-sided sensorineural hearing loss.
A case of endolymphatic sac tumor
Keywords: Tıbbi Laboratuar Teknolojisi; Genel ve Dahili Tıp; Tıbbi Araştırmalar Deneysel